2018
DOI: 10.1007/s00105-018-4127-4
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenese des atopischen Ekzems

Abstract: Atopic dermatitis (AD) is one of the most common chronic inflammatory diseases and is also one of the most frequent reasons to consult a dermatologist. Over the past few years there has been a rapidly growing understanding of the cellular, molecular and immunological relationships as well as genetic variations, which leads to a better comprehension of the disease. Consequently, there are innovative targeted therapies in clinical studies or already approved for therapy. To make reasonable use of the new targete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…Paeonol is an active component extracted from the TCM Cortex Moutan, which is widely used and has high clinical development prospects (20,21). Numerous pharmacological and clinical studies have confirmed the biological properties of paeonol, including anti-inflammatory, anti-bacterial and antitumor effects (22,23). Our previous study demonstrated that oral administration of paeonol results in anti-inflammatory and immunoregulatory effects in BALB/c mice with psoriasis-like lesions (16).…”
Section: Discussionmentioning
confidence: 99%
“…Paeonol is an active component extracted from the TCM Cortex Moutan, which is widely used and has high clinical development prospects (20,21). Numerous pharmacological and clinical studies have confirmed the biological properties of paeonol, including anti-inflammatory, anti-bacterial and antitumor effects (22,23). Our previous study demonstrated that oral administration of paeonol results in anti-inflammatory and immunoregulatory effects in BALB/c mice with psoriasis-like lesions (16).…”
Section: Discussionmentioning
confidence: 99%
“…[51][52][53][54][55][56][57][58][59] Finally, there is hope for new effective treatments for the severely affected patients with atopic eczema in the future. [51][52][53][54][55][56][57][58][59] Finally, there is hope for new effective treatments for the severely affected patients with atopic eczema in the future.…”
Section: Discussionmentioning
confidence: 99%
“…There is a silver streak of hope on the horizon with the appearance of new targeted therapies with biologics such as monoclonal antibodies against relevant cytokines or receptors, for example the interleukin 4 receptor (dupilumab), interleukin 5 (mepolizumab), interleukin 13 (tralokinumab), interleukin 31 (nemolizumab) as well as new kinase inhibitors and others. [51][52][53][54][55][56][57][58][59] Finally, there is hope for new effective treatments for the severely affected patients with atopic eczema in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The chronic or relapsing nature of AE, with itch as the predominant symptom, can have a huge impact on affected individuals (4). Several studies have shown that physical wellbeing and quality of life can be severely impaired, especially in patients with severe AE (5)(6)(7)(8). However, to date, the impact and intensity of symptoms in the daily life of individuals with AE have gained limited attention.…”
mentioning
confidence: 99%